A Clinicopathological study of breast lesions in a Tribal population in rural Telangana: A 3-year retrospective analysis - Sylvester Noel LAZARUS; Dr Helen Mohamed Gouse; Dr Rajyalaxmi kante (Tropical Journal of Pathology and Microbiology, 2021)
Introduction: Breast lesions is one of the commonest health conditions encountered by the female population around the world. The incidence of breast cancer is on the raise from the last decade mainly due to the increase awareness and education of the demographic population. All the breast lesions inflammatory, benign or malignant arises considerable anxiety to the patients. The main objective of our study is to analysis the spectrum of breast disease according to the clinical presentation, age and histopathological correlation in the rural and tribal population of Telangana. so that a more specific target population can be focused in the future. And also, to develop a multi-disciplinary set in the screening as well as treatment in the hospital.  Result: Lump in the breast with or without pain is the most common presentation of the breast diseases (63.1). The mean age of breast lesion in 29.5 years. Benign breast condition including tumor has peak incidence in 2nd and 3rd decade. While malignant tumors in 4th decade. Benign breast conditions are most common (77%) and malignancies at 23%. Fibroadenoma (95%) is the most benign tumor followed by Fibroadenosis most common (3.4%) non neoplastic breast lesions. 3 cases of gynecomastia in the male breast also present. Infiltrating ductal carcinoma is the most common malignant tumor of the breast.Conclusion: Although benign breast conditions are more common more awareness and education required in the socially backward population in the rural area. More screen awareness programs are recommended from the institute to the deeper regions of the demographic population.Key words:Fibroadenoma, Infiltrating carcinoma of breast, Fibroadenosis, Tribal